Produksi Glukosa Cair dari Pati Singkong Varietas Mentega dan Ketan Melalui Hidrolisis Enzimatis Menggunakan Amilase. - Sindy Nindia Maretha Haristanti; Samuel Karim (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2026)
Glucose is a type of sugar widely used in the food and beverage industry. Liquid glucose can be produced from various starch sources, including cassava. This study aims to determine the effect of cassava types butter and glutinous and the concentration of α-amylase enzyme 0.1%; 0.2%; and 0.3% on the production of liquid glucose through enzymatic hydrolysis. The study used a Randomized Block Design RBD with testing parameters including qualitative starch analysis, yield, and sugar content using a refractometer. Cassava starch was obtained through extraction, precipitation, and drying processes, then hydrolyzed using the α-amylase enzyme. The results showed that the best treatment was obtained in butter cassava with an enzyme concentration of 0.3%, resulting in a yield of 60.44 ± 1.57% and a sugar content of 28.70 ± 2.81 °Brix. Starch analysis showed a color change from dark blue to purple indicating the presence of starch. These results indicate that the type of cassava and enzyme concentration affect the production of liquid glucose.